ROLE OF INTERNAL AUDITORS AND SUSTAINABILITY REPORTING: MEDIATING EFFECTS OF AUDIT COMMITTEE PERFORMANCE - Khan, Md Gulam Sharoar Hossain (International Journal of Accounting & Finance Review, 2023)
This study examines the relationship between the role of internal auditors and practices of sustainability reporting in the organization. Moreover, this study also examined the mediating relationship between the audit committee’s performance in relation to the role of internal auditors and practices of sustainability reporting. To fulfill this objective, data collection (325 responses) has been done from financial institutions of Bangladesh, which covers 85% of the total population. Standards of International Professional Practice Framework suggest two important roles of internal auditors, assurance and consulting, which are considered exogenous constructs in this study. The direct and indirect effects of exogenous and endogenous constructs are determined by using SmartPLS-4. The Results revealed that internal auditors’ assurance and consulting roles have a positive and statistically significant relationship with the practice of sustainability reporting. Moreover, the results also reported that audit committee performance has also mediating relationship in both two roles of internal auditors and sustainability reporting. The result of this study support to influence the understanding level of policy maker, regulators, and different stakeholders about the role of internal auditors and audit committee in relation to the practice of sustainability reporting of a financial institution in the perspective of developing countries. JEL Classification Codes: M40, M41, M42, H83, F65.